PERUBAHAN BENTUK TARI PENYAJIAN TARI BEDANA BANDAR LAMPUNG - Arini Sofia (Institut Seni Indonesia Surakarta, 2014)
Bedana dance creation is dance creation Bedana tradition. The dance is a social dance thatcan be served single, in pairs, or groups using the property fan used in a variety of events. Bedanadance that was danced in pairs at the presents time only danced in group with additional propertiesfan, this makes bedana dance become more interesting and more free no bound by traditionalvalues. Previously, this dance is a dance that only served for only be displayed in certain place.Bedana dance is the only sacred dance held at the hatam quran, but at the present time Bedanadance can be displayed anywhere, anytime without having to be bound by customary norms.Keywords: Bedana dance tradition to be Bedana dance creation